Ответ:
Пошаговое объяснение:
1) 1/3 - (+ 2/3) = 1/3 - 2/3 = - 1/3
2) -2/5 - (-3/5) = -2/5 + 3/5 = 1/5
3) смотри второй
4) -3/7 - (+4/7) = -3/7 - 4/7 = -7/7 = -1
5) 5/8 - (-7/8) = 5/8 + 7/8 = 12/8 = 1 4/8 = 1 1/2
6) -1/9 - (+2/9) = -1/9 - 2/9 = -3/9 = -1/3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1) 1/3 - (+ 2/3) = 1/3 - 2/3 = - 1/3
2) -2/5 - (-3/5) = -2/5 + 3/5 = 1/5
3) смотри второй
4) -3/7 - (+4/7) = -3/7 - 4/7 = -7/7 = -1
5) 5/8 - (-7/8) = 5/8 + 7/8 = 12/8 = 1 4/8 = 1 1/2
6) -1/9 - (+2/9) = -1/9 - 2/9 = -3/9 = -1/3